Communication, leadership and coordination failure - Dong, Lu; Montero, Maria; Possajennikov, Alex (Springer, 2018)
We investigate the limits of communication and leadership in avoiding coordination failure in minimum effort games. Our environment is challenging, with low benefits of coordination relative to the effort cost. We consider two leader types: cheap-talk leader-communicators who suggest an effort level, and first-mover leaders who lead by example. Both types of leadership have some ability to increase effort in groups with no history, but are insufficient in groups with a history of low effort. Using the strategy method for followers’ responses, we attribute the persistence of coordination failure to the presence of followers who do not follow the leader.